Pronominal Address Forms of College Students in Medellin (Colombia) from the Sociopragmatic Point of View: Socioeconomic Status and Sex - Jang, Ji Son (Íkala, Revista de Lenguaje y Cultura, 2010)
Objectives: To present the results of research on pronominal address forms among undergraduate population in Medellín. This research took into account socioeconomic status and gender as research variables. Methodology: It is based on the analysis of the main data obtained through a questionnaire of 806 informants, and it was applied to the following four statistical techniques: 1) Sample Size for Estimating Multinomial Proportions (Thompson, 1987); 2) Contingency tables (Cochran, 1952); 3) Kruskal-Wallis Test (nonparametric test) (Kruskal & Wallis, 1952); and 4) Friedman's Test (nonparametric test) (1937, 1939, 1940). Results: Statistics shows that the research variables influence the pronominal selection. Conclusions: The following findings are worth mentioning: the lower the social class, the more usted is used compared to tú / vos. Addressing someone as tú, compared to addressing him / her as vos, is observed more frequently among the high class. Among men, the use of ''tuteo'' can imply a feminizing nuance; the use of ''voseo'' is ever-present; the use of usted is very common compared to, for example, the Peninsular Spanish variant.